The association between anthropometric profiles and somatotype with 100 meter sprint amongst Indonesian sprint athletes - Eddy Purnomo; Novita Intan Arovah; Alfonsia Purnamasari (Health Science Journal of Indonesia, 2021)
Background: One hundred meter sprint was influenced by various internal and external factors. Somatotype and anthropometry profiles are possibly to be one of the factors that predicts performance. The aims of this study were to assess the anthropometry and somatotype profiles obtained from an example of Indonesian team university male sprinters and to elucidated potential correlations between anthropometry profile and somatotype with the 100m sprint. Methods: It was recorded that 20 selected sprint athletes participated as representatives from Indonesia in the XVIII ASEAN University Games with an averaged age (20.0 ± 0.92 year old). Anthropometric assessment includes height, weight, skinfold (triceps, supra-spinale, subscapula, suprailiaca, abdomen, calf, front thigh and chest)), two bicondylar widths (humerus and femur) and two circumferences (biceps and femur). The somatotype assessment was based on the Health & Carter method. Body fat percentage was assessed using the equation determined by Berzerk et al. (1963). Body Mass Index is calculated from body mass divided by height squared (kg/m2). Multicorrelation matrix and simple linear regression were used to assess the potential correlation between somatotype profile and anthropometry with the 100m sprint. Results: The average value of ectomorph-mesomorph-endomorph was 3.40-4.08-0.84 BMI at 20.6 0.6, while the fat percentage was 9.2 ± 0.8. There were no significant correlation and regression slope found between somatotype profile and anthropometry with the 100m sprint. Conclusion: Most of the athletes representing Indonesia at the ASEAN University Games were mesomorphs and ectomorphs. They had low endomorph score fat percentage. Body shape requirements was not related to the 100m sprint. Further investigation is recommended to amplify the findings. Keywords: body composition, somatotype, sprinter Abstrak Latar belakang: Lari seratus meter dipengaruhi oleh berbagai faktor internal dan eksternal. Profil somatotipe dan antropometri diperkirakan merupakan salah satu diantara faktor yang dapat memprediksi kinerja. Tujuan dari penelitian ini adalah untuk menilai antropometri dan somatotipe yang diperoleh dari sampel pelari putra perguruan tinggi Indonesia dan menjelaskan potensi korelasi antara antropometri dan somatotype dengan lari 100 meter. Metode: Tercatat 20 atlet sprinter terpilih sebagai perwakilan dari Indonesia di ASEAN University Games XVIII dengan rata-rata umur (20.0±0.92 tahun). Penilaian antropometri meliputi tinggi, berat badan, lipatan kulit (trisep, supra-spinale, subskapula, suprailiaka, abdomen, betis, paha depan dan dada), dua lebar bicondylar (humerus dan femur) dan dua lingkar (bisep dan femur). Penliaian somatotipe didasarkan dari metode Heath & Carter. Presentasi lemak tubuh dinilai sebagai persamaan yang ditentukan oleh Berzerk et al. (1963). Indeks Masa Tubuh dihitung dari masa tubuh yang dibagi dengan tinggi badan kuadrat (kg / m2). Matrix multikorelasi dan regresi linear sederhana digunakan untuk menilai potensi korelasi antara profil somatotipe dan antropometri dengan lari cepat 100 m. Hasil: Rata-rata nilai ectomorph-mesomorph-endomorph adalah 3.40-4.08-0.84. BMI di angka 20.6 ± 0.6, sedangkan presentasi lemak di angka 9.2± 0.8. Tidak ada korelasi yang signifikan dan kemiringan regresi ditemukan antara somatotipe dan antropometri dengan lari 100 m. Kesimpulan: Atlet yang mewakili Indonesia di ASEAN University Games sebagian besar mesomorph and ectomorph. Mereka memiliki presentasi lemak skor endomorph rendah. Syarat-syarat bentuk tubuh tidak berkaitan dengan lari 100 m. Investigasi lebih lanjut direkomendasikan untuk memperkuat temuan. Kata kunci: antropometri, somatotipe, pelari